Crisis in government accountability: essays on governance reforms and India's economic performance - Mookherjee, Dilip (New Delhi, 2004)
These essays by Dilip Mookherjee share a common theme - the importance and challenge of second and third generation reforms in the Indian economy in the era of increasing role of market forces. The author reviews in detail the following four areas: delivery systems for goods and services supplied by the government; tax collection; legal institutions; and regulation of the financial sector. A comprehensive introduction pulls together both theoretical and empirical context to the issues discussed in the text.
Keywords: Economic reforms